Chorea as a sign of systemic lupus erythematosus activity: case report - P. Caramelli; S.M. Toledo; P.E. Marchiori; E.R. Barbosa; M. Scaff (Arquivos de Neuro-Psiquiatria)
Chorea may occur as a neurological manifestation of systemic lupus erythematosus and is often associated with detection of antiphospholipid antibodies. No evidence of chorea as a sign of lupus activity has been established. We describe a patient with systemic lupus erythematosus associated with antiphospholipid antibodies who developed chorea, which has been considered a sign of lupus activity.